1988
DOI: 10.2307/1590817
|View full text |Cite
|
Sign up to set email alerts
|

F Strain Mycoplasma gallisepticum Vaccination of Post-Production-Peak Commercial Leghorns and Its Effect on Egg and Eggshell Quality

Abstract: Forty-five-week-old commercial leghorns negative for antibodies to Mycoplasma gallisepticum (MG) and M. synoviae were vaccinated with high-passage F strain MG (FMG). Hens were confined in modified Horsfall-Bauer isolation units through 60 weeks of age. Egg production (% hen day) and parameters of egg and eggshell quality were monitored, including egg weight, eggshell strength, Haugh unit score, pimpling, and blood/meat spot incidence. Egg production was significantly lower (P less than 0.05) for FMG vaccinates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The live F strain vaccine currently on the market is reported to provide good protection for layers [20][21][22], is capable of displacing the pathogenic R strain from infected flocks [23], and can be readily distinguished from field strains [24,25]. However, it has been shown to be pathogenic for young chickens when administered by an aerosol route [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The live F strain vaccine currently on the market is reported to provide good protection for layers [20][21][22], is capable of displacing the pathogenic R strain from infected flocks [23], and can be readily distinguished from field strains [24,25]. However, it has been shown to be pathogenic for young chickens when administered by an aerosol route [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion by Branton et al [45], that the reproductive tract exhibited normal functionality, was based on the observation that the histopathology of the ovary and of the various segments of the oviduct at 65 wk of age was not significantly affected by the HpFMG vaccination. Furthermore, in a different study in which hens were vaccinated with Hp-FMG at 45 wk of age, gross and microscopic examination of various segments constituting the oviduct at 60 wk of age revealed no observable abnormalities, suggesting that an HpFMG vaccination at 45 wk of age did not adversely affect subsequent oviduct function, although the appreciable 6.0% decrease in EP suggested some ovarian impairment or dysfunction [46]. However, Burnham et al [81] reported that in association with performance changes, HpFMGinoculated hens possessed fewer mature ovarian follicles, had smaller magnal, isthmal, and vaginal proportions of the reproductive tract, and experienced a 50% increase in the incidence of fatty liver hemorrhagic syndrome in comparison with HpFMG-free hens by 60 wk of age.…”
Section: Digestive and Reproductive Organ Characteristicsmentioning
confidence: 95%
“…Furthermore, in reports in which commercial pullets were inoculated by eye drop with HpFMG at 10 wk of age, Branton et al [45] showed that eggshell pimpling incidence was increased, but that EP, egg weight, eggshell strength, and Haugh unit scores were not significantly affected, and Branton et al [39] later showed that the percentages of jumbo, extralarge, medium, small, peewee, and undergrade egg sizes were not affected, whereas the percentage of large eggs was reduced. However, when birds were inoculated by eye drop with HpFMG at 45 wk of age, Branton et al [46] noted that EP was reduced and Haugh unit scores were increased without concomitant significant changes in eggshell strength, thickness, or pimpling or in blood and meat spot incidence. Therefore, based on these results, the effects of prelay inoculations of FMG on layer performance are minor, whereas those administered during postpeak lay have the potential to exert greater effects.…”
Section: Description Of Problemmentioning
confidence: 99%
“…F-strain vaccine has been used widely and is effective in displacing virulent (field) strains from poultry operations (Levisohn & Kleven, 1981;Kleven et al, 1990Kleven et al, , 1998. F-strain is very immunogenic but mildly virulent in chickens and virulent to turkeys (Rodriguez & Kleven, 1980;Lin & Kleven, 1982b;Branton et al, 1988;Abd-el-Motelib & Kleven, 1993); whereas ts-11 or 6/85 may induce a milder respiratory post-vaccination reaction and result in somewhat lower immunity than F-strain (Abd-el-Motelib & Kleven, 1993). The ts-11 vaccine has been reported to have minimal or no virulence for chickens and turkeys, and to induce good protection to MG in experimental and field situations (Abd-el-Motelib & Kleven, 1993;Whithear, 1996;Barbour et al, 2000).…”
Section: Introductionmentioning
confidence: 99%